The contribution of Cr and Mo to the passivation of Ni22Cr and Ni22Cr10Mo alloys in sulfuric acid. (November 2020) - Li, Xuejie; Henderson, Jeffrey D.; Filice, Fraser P.; Zagidulin, Dmitrij; Biesinger, Mark C.; Sun, Fan; Qian, Bingnan; Shoesmith, David W.; Noël, James J.; Ogle, Kevin
Highlights: The role of Mo on passivation was investigated by AESEC coupled with XPS. Mo enriched on the surface in the low potential domain and dissolved congruently in the high potential domain. Enrichment of Mo in the low potential domain enhanced the barrier properities of passive film. The dominant Mo species in the low potential domain was Mo(IV) and that in the high potential domain was Mo(VI). Abstract: The beneficial effects of Mo on passive film formation were investigated for Ni22Cr10Mo with AESEC and XPS by comparison with Ni22Cr and pure Ni and Mo. Both spontaneous (E ≈ -0.2 VSCE ) and anodic passivation (E = 0.3 VSCE ) showed Cr surface accumulation, while significant Mo accumulation (as Mo(IV)) only occurred during spontaneous passivation with a markedly reduced open circuit corrosion rate as a consequence. Mo facilitated the active to passive transition in the low potential domain probably by favoring the oxidation of Cr to Cr2 O3 over Cr(OH)3 . At higher potential, Mo dissolved as Mo(VI) and did not accumulate in the film.